First record of a cave maternity roost of Rhinolophus hipposideros (Bechstein, 1800) in Slovenia - Primož Presetnik; Borut Kumar (Natura Sloveniae)
The first cave maternity roost of Rhinolophus hipposideros in Slovenia was discovered in the summer of 2011 in the »Pod kevdrom« cave. The cave is located in the Idrijca River canyon, SSW of the town of Idrija (Western Slovenia). Here, we present information on preliminary observations as to the number of adult and juvenile animals, along with temperature statistics and cave morphology.